(3GdeQUY aj GdBHGA hGdCegGJ hGdCHfGA hGdHfGJ hGdCPhGA hGdPhGJ aj GddZIs - (3GdeHGQc Hf eMeO Hf eMeO Hf eMeO Hf nYrHO GdncpQje GdTjHGfqj GdLRQj, CHh GdSYGOGJ, eLO GdOjf, GHf GdCKjQ,J (B606 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg GdefRg Yf GdBHGA hGdGegGJ CeG HYO , aEf GdYdeGA ai SGda GdOgQ hBfag eGRGdhG eNJdai GdCZQGV ai eG Cdahg s
(3BNQgG (B:s
(3ef MQa GdhGh hGdgGA , bhdg (B: (3GdgdGc CHh eRfI , GHf djdI , GHf eRfI Gdgehe hGdCacGQ HfGJ GdUOQ , HfGJ GdVejQ , HfGJ GdacQ , HfGJ GdaDGO HfGJ GdfaS BNQ GdcJH s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HgG fXGe GdJYbjHIs
(3ecedI ai ChdgG Hbde eZGjQ CMOK hfbdJ ef fSNI fajSI YdjgG SeGY Ydi GdeUfa HNW CNjI YR GdOjf Ydi (B" (3UGMH cJGH GdcGed ai GdJGQjN (B" 605s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GddZIs